OPTIMALISASI BIOGAS DARI KOTORAN SAPI DENGAN PENAMBAHAN BAHAN ORGANIK DARI LIMBAH PERTANIAN DAN PASAR - S A Chayatul Luthfi (AGRISAINTIFIKA: Jurnal Ilmu-Ilmu Pertanian, 2022)
Cow farm waste is one type of raw material that is commonly used in biogas formation technology. According to 1Wahyuni (2013), a cow can produce fresh waste between 20 to 29 kg/day. According to 2Kaharudin and Sukmawati (2010), biogas on a household scale with a number of livestock of 2-4 cows or a supply of dung of approximately 25 kg/day is sufficient to use a reactor tube with a capacity of 2500-5000 liters which can produce biogas equivalent to 2 liters of oil. land/day and is able to meet the energy needs of one rural household with 6 family members. The higher the organic matter content in biogas technology, in a suitable environment, the biogas production will increase. This causes the need for the addition of mixed organic matter so that biogas production is maximized. The type of organic material used is a very important factor. Grass, rice straw or vegetable waste can be used as a source of organic matter in the biogas production process.